Generation of W States with Many Superconducting-Quantum-Interference-Devices in Cavity QED - 詹志明 (Communications in theoretical physics, 2010)
We propose a scheme to generate the W states with many SQUIDs （superconducting-quantum-interferencedevices） in cavity QED via Raman transition. In this scheme, the transfer of quantum information between the SQUIDs and cavity is not required. And the cavity field is only virtually excited, thus the cavity decay is suppressed during the W states generation. The SQUIDs are always populated in the two ground states. Therefore, the scheme is insensitive to the spontaneous emission of the excited level of the SQUID and cavity decay.